STUDI BIAYA MENGIKUTI PELELANGAN PEKERJAAN KONSTRUKSI PEMERINTAH - Enni Supriyani; Akhmad Suradji; Benny Hidayat (ITP Press)
In the implementation of government construction work, to get to the contractor (contractor) who is able to carry out the work in accordance with the specified requirements at a reasonable price and can be justified in terms of both quality and time of implementation, the project owner held the auction process. Contractors who want to follow the auction costs, of this then do research on the type and amount of costs incurred by the contractor during the auction. This research was conducted by looking at the relationship and influence between the value of the work packages with the amount of expenses incurred during the auctions. This research resulted in the type of expenses incurred during the auctions include Cost ATK, electricity, internet, employee salaries and telephones, transportation, consumption, SKA, SKT, administration fees letter of support, bank administration fees, administrative costs of insurance, and the cost of preparation of the contract, marketing costs (the manager of the auction, the client, sponsors and money thugs). The type of cost is the cost for the auction manager and the client. From the results of the regression analysis can predict the costs incurred during the auctions is Y = 4059762.314 + 0.002 X, and Y = 10,227,390.399 + 0.015 X respectively without taking into account the costs of marketing and marketing costs. Where X is the value of the work packages that followed (Value Project) maximum up to 3 billion Rupiah. Keywords: Cost, Auctions, Construction Works.